2014
DOI: 10.1111/liv.12577
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms controlling the phenotype and the EMT/MET dynamics of hepatocyte

Abstract: The complex spatial and paracrine relationships between the various liver histotypes are essential for proper functioning of the hepatic parenchymal cells. Only within a correct tissue organization, in fact, they stably maintain their identity and differentiated phenotype. The loss of histotype identity, which invariably occurs in the primary hepatocytes in culture, or in vivo in particular pathological conditions (fibrosis and tumours), is mainly because of the phenomenon of epithelial-to-mesenchymal transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 79 publications
6
68
0
1
Order By: Relevance
“…Interestingly, among the tested cytokines, TGFbeta1 induced, together with a morphological epithelial-to-mesenchymal transition (EMT) as expected and previously described [2224], also a weighty rate of binucleation compared to untreated cells (23,3±3% in TGFbeta1-treated versus 2,1±1,8% in untreated cells) (Fig 1A, Fig 1B and S1 Fig, upper panels, and Fig 1C). …”
Section: Resultssupporting
confidence: 84%
“…Interestingly, among the tested cytokines, TGFbeta1 induced, together with a morphological epithelial-to-mesenchymal transition (EMT) as expected and previously described [2224], also a weighty rate of binucleation compared to untreated cells (23,3±3% in TGFbeta1-treated versus 2,1±1,8% in untreated cells) (Fig 1A, Fig 1B and S1 Fig, upper panels, and Fig 1C). …”
Section: Resultssupporting
confidence: 84%
“…The altered expression of miRNAs in liver fibrosis and necrosis that was observed in this study is in agreement with their functional role and could be further investigated as potential biomarkers of liver fibrosis [41] and cell death [42,43]. Assessment of these and other miRNAs might be done in formalin-fixed paraffin embedded (FFPE) samples, thus allowing to select a larger group of patients for validation studies, as well as to analyze retrospectively samples from the same patient in order to identify miRNAs more directly related to progression of the process and, in the cases of treated patients, with regression of the architectural changes.…”
Section: Accepted Articlesupporting
confidence: 86%
“…Wide evidence demonstrated that the orphan nuclear receptor hepatocyte nuclear factor 4-α (HNF4α), master regulator of hepatocyte differentiation and hepatic epithelium formation [13,14], also acts as a master regulator of MET (for review [15]). Notably, a role for HNF4α as a direct repressor of master EMT regulators and mesenchymal genes was recently unveiled, thus providing evidence for its pivotal function for both the regulation of the dynamic process of MET and the maintenance of a stable epithelial phenotype [16].…”
Section: Introductionmentioning
confidence: 99%